Social competence, cultural orientations and gender differences: a study of Mandarin–English bilingual preschoolers. Issue 2 (2nd April 2016) - Ren, Yonggang; Wyver, Shirley
ABSTRACT: This study investigated whether host and heritage cultural orientations were associated with Chinese preschoolers' social competence and whether such associations varied across gender in Western contexts. Ninety-six Chinese-Australian children aged 36–69 months from 15 childcare centres in Sydney participated in the study. The General Ethnicity Questionnaires were modified to obtain a parent report of children's orientation to the host and heritage cultures. Social competence was assessed using teacher reports on the Behaviour Assessment System for Children-2 (BASC-2) with four composite scales: Externalising, Internalising, Behavioural Symptoms and Adaptive Skills. Host culture orientation was negatively associated with Internalising, Behavioural Symptoms and positively with Adaptive Skills in the overall sample. When analysed by gender, host cultural orientation was found to be positively associated with Adaptive Skills for boys and girls and negatively associated with Externalising and Behavioural Symptoms only in girls. Heritage cultural orientation was not associated with the BASC-2 composites either in the overall sample or by gender. The results indicate that host culture has a stronger relationship with social competence than heritage culture, particularly for girls.